1985
DOI: 10.1128/iai.47.1.169-175.1985
|View full text |Cite
|
Sign up to set email alerts
|

Defective neutrophil and monocyte motility in patients with early onset periodontitis

Abstract: Several studies have documented suppressed polymorphonuclear neutrophil (PMN) chemotaxis in most patients with juvenile periodontitis. In contrast, data regarding PMN chemotaxis in patients with rapidly progressive periodontitis are very limited, and monocyte (MN) chemotaxis and random migration of PMNs or MNs from these patients have not been studied previously. Accordingly, we examined cell motility of PMNs and MNs from 27 patients with rapidly progressive periodontitis, 5 patients with juvenile periodontiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0

Year Published

1987
1987
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(34 citation statements)
references
References 19 publications
0
34
0
Order By: Relevance
“…The only abnormality detected in the immunological investigation was some reduction in neutrophil chemotaxis. It has been shown that such functional defects may be associated with increased susceptibility to periodontal destruction in children and young adults and are a relatively constant finding in prepubertal, juvenile and some cases of rapidly progressive periodontitis in young adults (Page et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The only abnormality detected in the immunological investigation was some reduction in neutrophil chemotaxis. It has been shown that such functional defects may be associated with increased susceptibility to periodontal destruction in children and young adults and are a relatively constant finding in prepubertal, juvenile and some cases of rapidly progressive periodontitis in young adults (Page et al 1985).…”
Section: Discussionmentioning
confidence: 99%
“…However, there is a group of cases which continue to show periodontal pocket formation and bone resorption despite all efforts at treatment by the periodontist and good oral hygiene practice by the patient. Increased attention is being given to this group of refractory or "downhill" cases (Page 1985) and the question is asked -How do these patients differ from those who are successfully treated and reqtiire only maintenance therapy thereafter?…”
mentioning
confidence: 99%
“…Little specific information is available about these cases, some of which manifest progressive attachment loss while in others deterioration occurs in a "rapid and unrelenting manner regardless of the type or frequency of therapy applied" (Page 1985).…”
mentioning
confidence: 99%
See 2 more Smart Citations